Magnetite and its galvanic effect on the corrosion of carbon steel under carbon dioxide environments - Chan, Emilyn Wai Lyn (Curtin University, 2011)
Carbon dioxide corrosion, which can cause premature failure of oil and gas pipelines, is an imperative health, safety and environmental issue in the oil and gas industry. Extensive studies have been conducted to understand the formation and role of iron carbonate scale, which is the most probable scale formation under CO2 corrosion. This scale can be protective toward the carbon steel pipelines. However, many post failure studies and ex-situ corrosion product scale analyses have shown the presence of thick corrosion product scale that consists mainly of black magnetite scale.The formation of magnetite scales from carbon dioxide corrosion of oil and gas carbon steel pipelines at temperatures below 100oC has not been studied or investigated comprehensively despite the fact that magnetite is often found in pipelines. The observation of rapid corrosion failures and the associated corrosion product scale on the ruptured pipelines has instigated this PhD research to determine the mechanism of the formation of corrosion product scale and the galvanic effect of the magnetite scale in causing an accelerated corrosion.Consequently, the mechanism of the formation of corrosion product scale on carbon steel under anaerobic conditions was studied. Preliminary studies on the corrosion product scales were conducted in an autoclave at 150oC. The morphology and the properties of the corrosion product scales were analysed using Raman spectroscopy, Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Ex-situ analysis showed that the scale formed in a pH 5.5 anaerobic brine solution saturated with a low partial pressure of carbon dioxide gas comprised a mixture of magnetite (Fe3O4) and iron carbonate (FeCO3). Whereas, the scale formed under the same temperature and solution pH, but in the absence of carbonate or bicarbonate species, consists only of magnetite. However, results from ex-situ analysis cannot be relied upon to conclusively prove the state of the surface in-situ. Therefore, a jet impingement cell that incorporates the capability of applying electrochemical measurements was used as an autoclave.The autoclave tests were replicated with in-situ electrochemical monitoring in the jet impingement cell to study the corrosion process and the scale development. The test temperature was set at 80oC to closely simulate the operating temperature in most oil and gas production fields. The morphology of the scales was examined under a Field Emission Scanning Electron Microscope (FESEM) since the SEM was not able to resolve nanometer structures on the surface. The FESEM clearly resolved the porous lath-like structure of chukanovite (Fe2(OH)2CO3), iron carbonate and ultrafine nanometer crystals on the scale surface formed under low partial pressure of carbon dioxide. On the other hand, the carbon steel surface, which was corroded in the absence of carbonate species at pH 5.5, was fully covered with nanometer crystalline magnetite that was only detectable under the FESEM. The identity of the iron compounds was confirmed using Synchrotron Radiation Grazing Incidence X-ray Diffraction (SR-GIXRD).An in-situ SR-GIXRD study on the corrosion of carbon steel under low partial pressure of carbon dioxide gas was carried out, incorporating EIS. This combined approach showed a strong correlation of the phase development as detected on the SR-GIXRD to the electrochemical behaviour on the impedance spectra. The development of the porous chukanovite and magnetite was found in association with a higher corrosion rate of the carbon steel before the steel was passivated by the combined corrosion product scale. Both in-situ and ex-situ studies have shown that magnetite (Fe3O4) and chukanovite (Fe2(OH)2CO3) are formed at the early stage of scale development via electrochemical and hydrolysis reactions in mildly acidic conditions before iron carbonate exceeds it solubility limit and precipitates rapidly over the carbon steel surface.The galvanic effect of coupling the magnetite to carbon steel was studied. The coupling was found to cause galvanic corrosion of the carbon steel. The cathode to anode surface area ratio of the magnetite/mild steel couple and the solution pH, inter-related to the partial pressure of carbon dioxide, were investigated and found to be contributing factors to the rate of galvanic corrosion. The galvanic corrosion was cathodically controlled by magnetite. The self corrosion rate of the carbon steel was reduced with increasing pH but the galvanic corrosion rate did not seem to be affected by the high pH. This prompted the suggestion of the possibility of magnetite itself partaking in self reduction and contributing to the galvanic current.Following the hypothesis that magnetite undergoes reductive dissolution in acidic carbon dioxide solution, studies were carried out to study on the reductive behaviour of magnetite. Cyclic voltammetry was used to investigate the reductive-oxidative behaviour of magnetite at different solution pH. The results show that magnetite does undergo reduction when it is polarized cathodically. Ferric ion in the magnetite lattice reduces to ferrous ion that can diffuse from the solid lattice in acid solution or form hydroxide compounds. The semiconductivity of magnetite was investigated using the Mott-Schottky technique, illustrating a conversion from an n-type semiconductor to a p-type semiconductor when the magnetite was reduced cathodically.In view of the galvanic effect from the magnetite scale, corrosion inhibitors that are commonly used to control carbon dioxide corrosion in the oil and gas industries were tested for their inhibition efficiency against this galvanic corrosion. Generic inhibitors as well as industrial formulated inhibitors were tested. Some inhibition was observed, but all materials failed to achieve a confidence level of at least 90% of inhibition efficiency.